Significados de un grupo de docentes atribuidos a las Manifestaciones Agresivas de los Niños(as) en el Aula - López Reina, Claudia Karina (Universidad Antonio Nariño, 2023)
The manifestations of violence presented in the current educational systems have become a subject of particular attention not only to educational institutions but also to mental health professionals. In the present narrative qualitative type of research, four teachers have been chosen, through semi-structured interviews.